Mouse Model of Heart Failure With Preserved Ejection Fraction Driven by Hyperlipidemia and Enhanced Cardiac Low‐Density Lipoprotein Receptor Expression - Monique Williams; Jose Manuel Condor Capcha; Camila Iansen Irion; Grace Seo; Guerline Lambert; Ali Kamiar; Keyvan Yousefi; Rosemeire Kanashiro‐Takeuchi; Lauro Takeuchi; Ali G. Saad; Armando Mendez; Keith A. Webster; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The pathways of diastolic dysfunction and heart failure with preserved ejection fraction driven by lipotoxicity with metabolic syndrome are incompletely understood. Thus, there is an urgent need for animal models that accurately mimic the metabolic and cardiovascular phenotypes of this phenogroup for mechanistic studies. Methods and Results Hyperlipidemia was induced in WT‐129 mice by 4 weeks of biweekly poloxamer‐407 intraperitoneal injections with or without a single intravenous injection of adeno‐associatedvirus 9–cardiac troponin T–low‐density lipoprotein receptor (n=31), or single intravenous injection with adeno‐associatedvirus 9–cardiac troponin T–low‐density lipoprotein receptor alone (n=10). Treatment groups were compared with untreated or placebo controls (n=37). Echocardiography, blood pressure, whole‐body plethysmography, ECG telemetry, activity wheel monitoring, and biochemical and histological changes were assessed at 4 to 8 weeks. At 4 weeks, double treatment conferred diastolic dysfunction, preserved ejection fraction, and increased left ventricular wall thickness. Blood pressure and whole‐body plethysmography results were normal, but respiration decreased at 8 weeks (P<0.01). ECG and activity wheel monitoring, respectively, indicated heart block and decreased exercise activity (P<0.001). Double treatment promoted elevated myocardial lipids including total cholesterol, fibrosis, increased wet/dry lung (P<0.001) and heart weight/body weight (P<0.05). Xanthelasma, ascites, and cardiac ischemia were evident in double and single (p407) groups. Sudden death occurred between 6 and 12 weeks in double and single (p407) treatment groups. Conclusions We present a novel model of heart failure with preserved ejection fraction driven by dyslipidemia where mice acquire diastolic dysfunction, arrhythmia, cardiac hypertrophy, fibrosis, pulmonary congestion, exercise intolerance, and preserved ejection fraction in the absence of obesity, hypertension, kidney disease, or diabetes. The model can be applied to dissect pathways of metabolic syndrome that drive diastolic dysfunction in this lipotoxicity‐mediated heart failure with preserved ejection fraction phenogroup mimic.